Prefix cyber-: all is obvious? - Архипов, Александр Евгеньевич (Ukrainian Information Security Research Journal, 2016)
We consider the prevailing situation today, associated with the development of terminology in the field of information and cybersecurity. Abstract-old problem of substitution of the term "security of information" by the term "information security". The focus of the article is made on the use of terms with the prefix cyber-. It is shown that with the help of cyber- is distinguished class of cybersystems that are used for solving the problems of administrative character in a variety of activ-ities. However, compared with traditional management systems that allow management implemented a set of interrelated processes of collection, storage and processing of information in the first place cybersystems extends the requirement of continuity and stability control. This requirement can be satisfied only on condition of availability, integrity and confidentiality of the source of information, attracted for the development of the administrative decision. The article analyzes the main characteristics of modern cybersystems, content and in-terrelation of "cyberspace" concepts "cybersecurity", "cyberthreat."